Sztuka permutacyjna jako forma oporu w kinie eksperymentalnym - PUDŁO, FILIP GABRIEL (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Permutation Art as a Form of Resistance in Experimental Cinema This study aims to present two examples of permutation films as forms through which experimental cinema resisted the reality of the 1970s. The analysis is based on two works by members of the Workshop of the Film Form: “1, 2, 3... Cinematographers Exercise” by Paweł Kwiek and “Apnoea” by Wojciech Bruszewski. Analysis and comparison of the two oeuvres is performed with the use of methods characteristic for these types of cinematic forms. This work also discusses the idea and historical context of permutation art and presents its relationship with particular current activities in the field of art.